Urinary tract infection – acute, recurrent, chronic, complicated - Czekalski, Stanisław (Przewodnik Lekarza/Guide for GPs, 2010)
Urinary tract infection (UTI) is second most common cause of medical consultation, after respiratory tract infections. ZUM signifies presence of the microorganisms in urinary tract above the sphincter of urinary bladder. In clinical practice, the initial diagnosis of UTI is established on the basis of signs and symptoms including differentiation among uncomplicated or complicated, acute, recurrent and chronic forms. This differentiation is important for the decision about diagnostics and therapeutic management. Uncomplicated UTI appears only in young women, without any pathology in the urinary flow and any illness or factor affecting immunity. All other UTI should be managed as complicated. In the complicated UTI, microbiological examination of the urine is obligatory for the verification of adequacy of empirical treatment introduced earlien After end of the treatment of UTI, the control of effect of therapy is necessary.